The Implementation of Sanitary Personal Hygiene and the Amount of Liquid and Solid Waste on the Production of North Cibuntu Tofu Factory Sumedang - Gita Arisara; Tetin Nur Andriani; Nabilah Nabilah; Siti Nurhasanah; Yulia Siti Fathonah (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
Hygiene is a public health action that specifically covers all efforts to protect, maintain and enhance the degree of physical and mental health, both for the public and for individuals with the aim of the basics of continuing a healthy life and enhancing welfare and energy. Sanitation is a public health effort that focuses on monitoring various environmental factors that can affect human health status. Tofu industrial waste water is one type of industry that disposes of its liquid and solid waste processing either directly or indirectly into water bodies, where in the tofu production process a lot of water is needed for the production process. The purpose of this study was to increase knowledge and change the behavior of employees at the Cibuntu tofu factory in order to understand personal hygiene and to find out how the process of processing liquid and solid waste from the production of the Cibuntu tofu factory in North Sumedang District. This study used descriptive qualitative method. Data collection techniques were carried out by interviews, observation, and documentation with informants. Results: Based on the observations of 25 employees, 19 (84%) of the tofu factory employees did not apply personal hygiene at work, most did not use company standard clothing, even 4 employees did not wear clothes, 16 employees (70%) did not use masks and did not use gloves, even the soy bean filter was not washed, while the waste treatment was carried out according to a predetermined WWTP procedure. There is a filtering process in wastewater treatment and a large tub is available for the filtering process so that the wastewater discharged into the river is quite safe. The conclusions from this study need to be improved and reapplied regarding personal hygiene for employees of the Cibuntu tofu factory.